A clinical example of the effective use of collapse surgery in a patient with a cavity formation of an operated lung complicated by recurrent pulmonary hemoptysis - D. V. Donchenko; R. V. Tarasov; M. V. Chashchina; S. S. Sadovnikova; E. N. Adamovskaya; E. V. Krasnikova; M. A. Bagirov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
Relevance. To date, all pathognomonic clinical and radiological signs have not been identified for any disease manifested in the form of cavities in the lung, which leads to diagnostic errors, the frequency of which varies from 19 to 93.7% in various pathological processes in the lungs. The clinical course of most forms of cavities can often be complicated by the development of respiratory failure and/or pulmonary hemoptysis/bleeding.Aim: to demonstrate the result of surgical treatment of a patient with a cavity formation of an operated lung complicated by recurrent pulmonary hemoptysis. Object and methods. A clinical case of successful application of extrapleural pneumolysis with the installation of a silicone implant from the operated lung as a method of eliminating sanitized cavities is described.Clinical case description. Patient M., 54 years old, long-term follow-up for rheumatoid arthritis, receiving courses of immunosuppressive therapy, noted the appearance of cough, a single episode of hemoptysis. Pulmonary tuberculosis was excluded based on the clinical and radiological picture. Due to the recurrence of hemoptysis, an upper lobectomy was performed on the left. In the histological examination of the surgical material: the morphological picture is characteristic of bronchiectasis of the lung with the development of nonspecific purulent granulomatous inflammation. Due to repeated episodes of hemoptysis, extrapleural pneumolysis was performed with the installation of a silicone implant, after which the episodes were not repeated.Conclusion. The EPSI collapsosurgical method made it possible to preserve the patient's functional reserves as much as possible and compress the lung cavity formation, which confirms its high effectiveness.